Antibacterial assay and molecular identification of selected antagonistic actinomycete strain against bacterial leaf blight disease pathogen, Xanthomonas oryzae pv. oryzae - Shabudin, Nurul Fatiah (2016)
Bacterial Leaf Blight (BLB) caused by Xanthomonas oryzae pv. oryzae is one of the most destructive disease affecting rice production worldwide with yield losses recorded up to 60% in Asia. Current control methods are now focusing on chemical pesticides implementation which lead to environmental pollution and increase human health awareness. Therefore, microbe-based biocontrol agent such as selected actinomycetes strain and other antagonistic microbe can be used as an alternative and safer solution to control BLB disease. Actinomycetes strain have been reported to produce larger number of bioactive compound which effective against important plant pathogenic bacteria and fungi. The aims of this research, 1) to obtain antibacterial crude extract using different extraction methods which are broth, activated charcoal and agar and 2) to identify actinomycete strain using molecular method via 16s rRNA. Through this experiment, only broth and activated charcoal extraction method were able to show an antibacterial activity against Xoo pathogen. For broth extraction method, only ethyl acetate solvent showed a 10 mm inhibition zone on the MHA agar at 7 days inoculation. Meanwhile, for activated charcoal extraction method, only ethyl acetate solvent managed to show an antibacterial activity for 7 days, 14 days, and 21 days with 6 mm, 15 mm, and 13 mm inhibition zone respectively. Molecular identification via 16s rRNA amplification revealed that selected actinomyces strain belonged to the genus Streptomyces.